The effect of homeownership on the option value of regional migration - Florian Oswald (Quantitative Economics, 2019)
This paper estimates a lifecycle model of consumption, housing choice, and migration in the presence of aggregate and regional shocks, using the Survey of Income and Program Participation (SIPP). The model delivers structural estimates of moving costs by ownership status, age, and family size that complement the previous literature. Using the model, I first show that migration elasticities vary substantially between renters and owners, and I estimate the consumption value of having the option to migrate across regions when there are regional shocks. This value is of lifetime consumption on average, and it varies substantially with household type.
Keywords: J6; R2; R23; 330; Migration; housing; lifecycle consumption; regional shocks